2002
DOI: 10.1046/j.1365-3059.2002.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Clavibacter michiganensis ssp. michiganensis in infected tomato stems under natural field conditions in California, Ohio and Morocco

Abstract: The survival and half-life of Clavibacter michiganensis ssp. michiganensis ( C. michiganensis ), the causal agent of bacterial canker of tomato, were determined in infected plant debris under natural field conditions in California, Ohio and Morocco using a semiselective agar medium. The organism survived significantly longer in tomato stems left on the soil surface than in stems buried in the soil at all locations studied. The pathogen was recovered in high amounts from tomato stems left on the soil surface fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 12 publications
2
35
0
2
Order By: Relevance
“…However, these control measures might not be sufficient to eradicate the pathogen. Although Cmm does not survive well in the soil, it can survive on plant debris for several years (Fatmi and Schaad 2002;Gleason et al 1993). The possibility that the pathogen can reside on alternative hosts or on volunteer wild plants cannot be excluded (Chang et al 1992;Tsiantos 1987), but this might not explain the severe outbreaks of the disease that occurred during recent years.…”
Section: Discussionmentioning
confidence: 99%
“…However, these control measures might not be sufficient to eradicate the pathogen. Although Cmm does not survive well in the soil, it can survive on plant debris for several years (Fatmi and Schaad 2002;Gleason et al 1993). The possibility that the pathogen can reside on alternative hosts or on volunteer wild plants cannot be excluded (Chang et al 1992;Tsiantos 1987), but this might not explain the severe outbreaks of the disease that occurred during recent years.…”
Section: Discussionmentioning
confidence: 99%
“…michiganensis from the infested plants was made on C. michiganensis subsp. michiganensis selective agar medium (Fatmi and Schaad 2002).…”
Section: Control Of Bacterial Canker Under Greenhouse Conditionsmentioning
confidence: 99%
“…michiganensis (Davis et al 1984) has been reported in the most tomato growing areas in the world (Gleason et al 1993;Menzies and Jarvis 1994). It's incidence in Morocco has been reported since 1942 (Berger 1942) where is a very important factor of crop yield loss in the region of Souss-Massa Draa valley, Agadir, Morocco (Fatmi and Schaad 2002). A few commercially grown cultivars have significant tolerance or resistance to C. michiganensis subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Not only geographic location, but also host debris placement within the soil profile affected the survival time. In different locations, this period was between 25 and 75% shorter in buried residues than in those left on the soil surface (Gleason et al ., ; Fatmi & Schaad, ). In Illinois the concentration of the pathogen was also an order of magnitude smaller in buried tissues than in those left on the soil surface (Chang & Pataky, ).…”
Section: Introductionmentioning
confidence: 99%